Recent Advances in Dye-Sensitized Solar Cells. (4th December 2007) - Lenzmann, F. O.; Kroon, J. M.
Abstract : This review describes recent advances in the research on dye-sensitized solar cells. After a brief discussion of the general operation principles and a presentation of record efficiencies, stability data and key technology drivers, current trends will be reviewed. The focus of this review is on materials development (sensitizers, nanostructured oxide films, and electrolyte), but commercialization aspects will also be briefly addressed. The review describes the most relevant characteristics and major trends in a compact way.